Redes sociales y su aporte en el fortalecimiento del aprendizaje del lenguaje en los estudiantes de la básica primaria (2018)
The purpose of this research is to present the results obtained from the contributions of social networks in the strengthening of language learning in primary school, held in third and fourth grades of the Flowers Hill Bilingual School, where students have weakness in the learning of reading due to multiple cultural aspects and procedures in the teaching-learning process and where it is given aspects that indicates that using social networks, facilitates learning because children manipulate the images, observe, read signs , messages and in this way they are motivated towards language learning. It is expected that in the application of the variables the teaching-learning process will be considerably strengthened in said degrees and in the Institution